Study of messenger and Wi-Fi sharing in android (International Journal of Current Engineering and Technology, 2015)
A Messenger application is a service wherein a user can not only communicate over the Internet in the form of messages but also can exchange data in the form of images, audio and video files. So basically the user has in numerous uses of these services and comparatively has to pay a meager price for merely the data services used. But what if a user did not have access to the cellular network by some means. For this there is also a feature incorporated in the application of Wi-Fi sharing which would enable any user to perform similar operations without the use of Internet and instead use the Wi-Fi network of a mobile device and exchange data that are quite larger in terms of size. This paper aims at providing a basic idea on the implementation and working of a Messenger and a Wi-Fi sharing application based in android, which include the protocols, algorithms and methods that can be used for implementation.
Keywords: Google Cloud Messenger; Adhoc; Wireless Networks; Instant Messaging; Wi-Fi.